The Influence of Self Efficacy on the Learning Outcomes of Class VIII Students in Social Studies Subjects at SMPN 27 Surabaya - Qomariah, Nurul (Program Studi S1 Pendidikan IPS, Universitas Negeri Surabaya, 2022)
Goal of the study was to ascertain how self-efficacy affected students' learning in social studies classes at SMPN 27 Surabaya. Ex post facto quantitative research is the style used two independent variables Selfefficacy based on the experience other people's success and Selfefficacy based on success in completing assignments on time and excellent, variables depending on students' social studies learning outcomes class VIII. The population used this students of class VIII SMPN 27 Surabaya, 308 students. Stratified proportional sampling utilized in the sampling procedure and Slovin, total 39 students with data collection form questionnaires and social studies learning tests. Data analysis with partial correlation and multiple regression test with SPSS 21.0 the results, First hypothesis self-efficacy based on the experience of others' achievement influences the social studies learning outcomes of class VIII pupils of the results of 2,517 and sig 0.016. Second Hypothesis Self-efficacy results from finishing tasks on time and performing very well on social studies learning outcomes for class VIII pupils 4,380 and sig 0,000. Third Hypothesis an f count of 50,909 and sig 0.000.